Assessment of lateral malleolus weber C fractures' outcomes in patients undergoing syndesmosis-only fixation versus syndesmosis and fibular fixation - Henawy, Ayman T (Egyptian orthopaedic journal, 2024)
Abstract Introduction Ankle fractures were associated with syndesmosis injuries, so it is very important to gain accurate anatomical reduction of the ankle mortise and good fixation of the disrupted syndesmosis. Aim Aim of this study was to assess lateral malleolus Weber C fractures' outcomes in patients undergoing syndesmosis-only fixation versus syndesmosis and fibular fixation. Subjects and methods The present study was designed as a randomized controlled clinical trial study that included all patients presenting to the emergency room at Suez Canal University hospital after an ankle twisting injury causing lateral malleolus Weber C fracture. Results Patients who had performed syndesmosis-only were found to have significantly higher tibiofibular clear space (AP and mortise views) at 6 months only compared to those who had syndesmosis and fixation. Also, There was no statistically significant difference between syndesmosis-only and syndesmosis with fixation groups in regard to medial clear space, incidence of soft tissue infection, delayed union, Complex regional pain syndrome or all items of OMAS scale. Conclusions There was a significantly stability and nearby functional outcomes with a minimally invasive technique in the group managed by syndesmosis-only fixation and the group managed by syndesmosis and fibular fixation. The results are optimistic regarding the benefits of syndesmosis-only fixtion in patients with lateral malleolus Weber C fractures. However, more confirmatory studies need to be done.